Association Relationship between Personal Variables and Numbers of ICTs, Accessibility of ICTs, Agriculture Practices and Animal Husbandry Practices: Study in Haryana (Indian Journal of Extension Education, 2017)
The present study was carried out in four districts of Haryana state i.e., Yamunanagar, Karnal, Hisar and Fatehabad, which were selected randomly. In total 240 respondents viz., 60 farmers from each district, 30 farmers from each block and 15 farmers from each village were selected for the present study. Correlation coefficient and regression coefficient of personal variables were found positively significant, negative significantly and non significant with numbers of ICTs, accessibility of ICTs, agriculture practices information and animal husbandry practices.